IMPLIKASI PENDIDIKAN AGAMA WANITA TERHADAP KEHARMONISAN KELUARGA : Studi Kasus di Desa Wonokerso Pakisaji Malang - Mukarromatun Nisa Nisa; Siti A'isyah (LP3M IAI Al-Qolam, 2022)
This paper is research on women's religious education in families in Wonokerso Pakisaji Malang with a low divorce rate. The research respondents are Muslim married couples, with 4 qualifications: 1) Couples with good religious education for women and less religious education for men, 2) Couples with less religious education for women and good religious education for men, 3) Couples with education are equally good, and 4) Couples with religious education are equally lacking. Data collection techniques through interviews with purposive techniques. A case study that found something new that women's religious education supports the formation of harmony in a household. Women with good religious education will support the realization of a harmonious family. Judging from how both fulfil their obligations as a Muslim Muslimah, are responsible for tasks in a household, good relations with partners with mutual understanding and solving problems together with deep talk, good relations with spouses, and together increase piety to Allah SWT.